Impacts of travel duration on urban-rural resident free vaccination behavior: Chinese COVID-19 vaccine booster dose evidence - Yudong Miao; Jingbao Zhang; Zhanlei Shen; Yi Li; Wanliang Zhang; Junwen Bai; Dongfang Zhu; Ruizhe Ren; Dan Guo; Clifford Silver Tarimo; Wenyong Dong; Qiuping Zhao; et al. (Taylor & Francis Group, 2024)
This study aimed to evaluate how the duration of travel affects the behavior of urban and rural residents regarding free COVID-19 vaccination, and provide scientific evidence for promoting free vaccination and building an immune barrier to cope with future epidemics. From August 3, 2022 to February,18,2023, A follow-up survey was conducted in urban and rural adults in four cities in China to collect information on socio-demographic factors, vaccination status and travel time for vaccination. Propensity score matching (PSM) analysis was deployed to measure the net difference of the enhanced vaccination rate between urban and rural residents in different traffic time distribution. A total of 5780 samples were included in the study. The vaccination rate of the booster dose of COVID-19 vaccine among rural residents was higher than that of urban residents with a significant P-value (69.36% VS 64.49%,p < .001). The traffic time had a significant negative impact on the COVID-19 booster vaccination behavior of urban and rural residents. There was a significant interaction between the travel time to the vaccination point and the level of trust in doctors. Travel time had a negative impact on the free vaccination behavior of both urban and rural residents. The government should optimize and expand the number of vaccination sites and enhance residents' trust in the medical system. This is crucial for promoting free vaccination and effective epidemic management in the future.